Comparing Culicoides biting rates in horses and cattle in The Netherlands: potential relevance to African horse sickness epidemiology - Elbers, A.R.W.; Gonzales, J.L.; Meiswinkel, R. (Entomologia experimentalis et applicata, 2018)
To determine relative host preference rates and to establish whether a pair of animals in close proximity (between–host interaction) modified Culicoides attack and abundance profiles, compared to those tethered in isolation (host independence), Culicoides midges were pooted hourly from two sets of experimental animals: (1) a heifer cow and Fjord horse tethered close together (5 m apart), and (2) a heifer and Fjord tethered in isolation (45 m apart). Over 12 days, 570 3‐min observations yielded 23 090 midges, representing 24 species. Approximately 95% belonged to the Culicoides obsoletus (Meigen) complex (two species), Culicoides dewulfi Goetghebuer, Culicoides chiopterus (Meigen), Culicoides punctatus (Meigen), Culicoides pulicaris (L.), and Culicoides achrayi Kettle & Lawson (Diptera: Ceratopogonidae) combined. There was no evidence for between‐host interaction. Mean Culicoides species‐specific attack rates did not differ between animal species, except that C. chiopterus was 7× more abundant on the legs of the heifer compared to the horse, and C. dewulfi twice as abundant on the upper half of the horse compared to the heifer. By contrast, mean species–specific biting rates of the C. obsoletus complex, C. chiopterus, C. dewulfi, C. punctatus, and C. pulicaris midges were 5×, 100×, 1.7×, 2×, and 2.5× lower in the horses compared to the heifers, respectively. It is not clear why high Culicoides attack rates observed in the horses do not convert into high biting rates as seen in cattle; this should be a subject for future research. In light of its apparent predilection for equids, the ability of C. dewulfi to replicate African horse sickness virus (AHSV) extrinsically should be investigated in the laboratory. Relative Culicoides (Diptera: Ceratopogonidae) attack and biting rates were determined in two sets of experimental animals, each set comprising a cow and a horse tethered close together (5 m) or far apart (45 m). There was no evidence for between‐host interaction in mean total midge counts: tethering distance between animal species did not matter. Although mean species–specific Culicoides attack rates were similar, the biting rates of the most abundant species were significantly lower in horses compared to cows.